The Effect of Omeprazole on the Pharmacokinetics of Piroxicam Profiles with High Performance Liquid Chromatography (HPLC) Method - Fahdi, Firdaus; Herviani Sari; Sulasmi; Wahyudi (Talenta Publisher, 2020)
Piroxicam is an anti-inflammatory drug of the NSAID class that is commonly used as an analgesic and anthireumatic drug. Its use is often combined with gastric drugs, one of which is omeprazole, considering the side effects of piroxicam which can irritate the stomach. Piroxicam and omeprazole work on the same enzyme, CYP-450 so that it can affect the pharmacokinetic profile especially in the metabolic and excretion phases of piroxicam. This research is an experimental study using 3 male rabbits. Measurement of plasma levels of piroxicam drug is carried out using a High Performance’s Liquid Chromatography (HPLC) tool. The validation method is used to determine LOD and LOQ values, accuracy, and precision tests. The results of data analysis using t-tables. The results showed the value of pharmacokinetic parameters in the absorption phase increased or there were differences but did not show any significant effect on each group. While the pharmacokinetic parameter values ​​in the metabolic and excretion phases decreased and showed no differences between groups. The administration of omeprazole and piroxicam together and the administration of piroxicam which was given an hour earlier by omeprazole can inhibit the enzyme that stimulates the metabolism of piroxicam so that it affects the pharmacokinetic parameters in the absorption phase and also excretion but is not significant.